Report of the Expert Group on Technology Options for Coal Industry (Executive Summary) - Planning Commission (Planning Commission, 1986)
The actual coal consumption in 1984-85 has been estimated at 139.52 mt. The VII Plan has estimated the coal demand at 236.7 mt by 1989-90, 325 mt by 1994-95 and 417 mt by 1999-2000. Assuming a slightly lower annual growth rate for the period beyond 2000 AD, the coal demand for 2004-05 is estimated at 520 mt. The sector wise coal demand for these time horizons is shown in Annexure-I.
Planning Commission
Planning Commission